Metabolomic signature of the seminal plasma in men with severe oligoasthenospermia - Magalie Boguenet; Cinzia Bocca; Pierre‐Emmanuel Bouet; Orianne Serri; Stéphanie Chupin; Lydie Tessier; Odile Blanchet; Hady El Hachem; Juan Manuel Chao de la Barca; Pascal Reynier; Pascale May‐Panloup (2020)
Male factor is incriminated in approximately 50% of cases of infertility. The metabolomic approach has recently been used in the assessment of sperm quality and male fertility.We analyzed the metabolomic signatures of the seminal plasma in 20 men with severe oligoasthenospermia (prewash total motile sperm count < 5.106 ) (SOA) and compared it to 20 men with normal semen parameters, with a standardized approach of targeted and quantitative metabolomics using high-performance liquid chromatography, coupled with tandem mass spectrometry, and the Biocrates Absolute IDQ p180 kit.Among the 188 metabolites analyzed, 110 were accurately measured in the seminal plasma. A robust model discriminating the two populations (Q2(cum) = 55.2%) was obtained by OPLS-DA (orthogonal partial least-squares discriminant analysis), based on the drop in concentrations of 37 metabolites with a VIP (variable important for projection) greater than 1. Overall, in men with SOA, there was a significant decrease in: 17 phosphatidylcholines and four sphingomyelins; acylcarnitines, with free L-carnitine being the most discriminating metabolite; polyunsaturated fatty acids; six amino acids (glutamate, aspartate, methionine, tryptophan, proline, and alanine); and four biogenic amines (spermine, spermidine, serotonin, and alpha-aminoadipate).Our signature includes several metabolic changes with different impacts on the sperm quality: a change in phospholipid composition and the saturation of their fatty acids that is potentially linked to the deterioration of sperm membranes; a carnitine deficiency that can negatively impact the energy production via fatty acid oxidation and oxidative phosphorylation; and a decreased level of amino acids and biogenic amines that can lead to dysregulated metabolic and signaling pathways.We provide a global overview of the metabolic defects contributing to the structural and functional alteration of spermatozoa in severe oligoasthenospermia. These findings offer new insights into the pathophysiology of male factor infertility that could help to develop future specific treatments.